1993
DOI: 10.1039/dt9930002465
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and dioxygen-binding properties of double-sided porphyrinatoiron(II) complexes bearing covalently bound axial imidazole

Abstract: Double-sided porphyrinatoiron( 11) complexes bearing covalently bound axial imidazole, 5-[2-(5imidazolylvaleryloxy) -6-(piva1oyloxy)phenyll -1 0.1 5,20-tris[2.6-bis(pivaloyloxy)phenyl] porphyrinatoiron(//) and 5-[2-(3.3-dimethylbutyryloxy) -6-(5-imidazolylvaleryloxy)phenyl] -1 0.1 5,20-tris[2,6bis(3,3-dimethylbutyryloxy)phenyl] porphyrinatoiron (11).have been synthesized. On the basis of their absorption and 'H NMR spectra, the axial imidazole group is co-ordinated. The complexes reversibly form stable dioxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
5
30
0
Order By: Relevance
“…941 The overall spectroscopic properties of [( 5/6 L)Fe II -(CO)] and [( 5/6 L)-Fe II –CO---Cu I (CO)] + (Figure 113) complexes were similar to those of their parent compounds, [(F 8 TPP)Fe II (CO)] and [(TMPA)Cu I (CO)] + . 415,964967 13 C-NMR experiments suggested the presence of two distinct isomeric forms of the Fe- only carbonyl complex of 5/6 L platforms, where the CO could either be at the same or the opposite side of the tethered copper chelate (Figure 113). Furthermore, infrared spectroscopic insights revealed the presence of two isomeric forms of [( 5/6 L)Fe II –CO⋯Cu I (CO)] + complexes as well, where the Cu I –CO unit is supported by either a tri- (major isomer; IR v (CO) Cu 2070 cm −1 ) or tetradentate (minor isomer IR v (co) Cu 2091–2093 cm −1 ) fashion, with the presence of a dangling, dissociated pyridine in the case of the former (Figure 113).…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 99%
“…941 The overall spectroscopic properties of [( 5/6 L)Fe II -(CO)] and [( 5/6 L)-Fe II –CO---Cu I (CO)] + (Figure 113) complexes were similar to those of their parent compounds, [(F 8 TPP)Fe II (CO)] and [(TMPA)Cu I (CO)] + . 415,964967 13 C-NMR experiments suggested the presence of two distinct isomeric forms of the Fe- only carbonyl complex of 5/6 L platforms, where the CO could either be at the same or the opposite side of the tethered copper chelate (Figure 113). Furthermore, infrared spectroscopic insights revealed the presence of two isomeric forms of [( 5/6 L)Fe II –CO⋯Cu I (CO)] + complexes as well, where the Cu I –CO unit is supported by either a tri- (major isomer; IR v (CO) Cu 2070 cm −1 ) or tetradentate (minor isomer IR v (co) Cu 2091–2093 cm −1 ) fashion, with the presence of a dangling, dissociated pyridine in the case of the former (Figure 113).…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 99%
“…With the aim of studying these effects, several chelated iron-porphyrin model systems have been synthesized, containing an appended imidazole residue which can intramolecularly bind to the iron center [8][9][10][11][12][13][14][15][16][17][18][19]. A different approach involves the use of heme-peptide complexes (called microperoxidases) obtained from the proteolysis of horse heart cytochrome c [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The O 2 -binding affinities [P 1/2 : O 2 pressure at half O 2 binding for the (porphyrinato)-iron(II)] and its thermodynamic parameters (∆H, ∆S) were determined (Table 1). 3d, [14][15][16] The P 1/2 value of (rHSA-FeP) 2 (30 Torr at 37°C) was almost identical to that of red blood cells (27 Torr), 18 and its O 2 -binding equilibrium curve showed Langmuir type absorption; the Hill coefficient was 1.0 ( Figure 6). It is known that cooperativity observed in the O 2 binding to hemoglobin has implications for physiological use.…”
Section: Resultsmentioning
confidence: 90%
“…3d, [14][15][16] It has also recently been found that the O 2 recombination of rHSA-FeP obeyed three-phase kinetics. 3d In the case of (rHSA-FeP) 2 , the assumption of multiphase rebinding of dioxygen is too complicated, so we employed the monophasic first-order reaction of O 2 association.…”
Section: Resultsmentioning
confidence: 96%